DISTRIBUSI TEKANAN PADA AIRFOIL NACA 23012 DENGAN PENAMBAHAN VORTEX GENERATOR - Leandis Leandis; Khairil Anwar; Rustan Hatib (Foristek, 2022)
This study aims to determine the effect of the use of a vortex generator on the pressure distribution of the NACA 23012 airfoil. The research method is experimental testing of the NACA 23012 airfoil model with the addition of a vortex generator in the wind tunnel with variations in air velocity 20.96 m/s2, 28.48 m/s2, and 33.90 m/s2, as well as with the angle of attack. The results showed that the airfoil with a vortex generator had a lower pressure coefficient (Cp) than without using a vortex generator.